Paediatric aortic valve replacement using decellularized allografts: a multicentre update following 143 implantations and five-year mean follow-up - Horke, Alexander; Bobylev, Dmitry; Avsar, Murat; Cvitkovic, Tomislav; Meyns, Bart; Rega, Filip; Hazekamp, Mark; Cesnjevar, Robert; Schmiady, Martin; Staebler, Brigitte; Dewald, Oliver; Ciubotaru, Anatol; et al. (European Journal of Cardio-Thoracic Surgery, 2024)
OBJECTIVES: Decellularized aortic homografts (DAH) were introduced in 2008 as a further option for paediatric aortic valve replacement (AVR). METHODS: Prospective, multicentre follow-up of all paediatric patients receiving DAH for AVR in 8 European centres. RESULTS: A total of 143 DAH were implanted between February 2008 and February 2023 in 137 children (106 male, 74%) with a median age of 10.8years (interquartile range 6.6-14.6). Eighty-four (59%) had undergone previous cardiac operations and 24 (17%) had undergone previous AVR. The median implanted DAH diameter was 21mm (interquartile range 19-23). The median operation duration was 348min (227-439) with a median cardiopulmonary bypass time of 212min (171-257) and a median cross-clamp time of 135min (113- 164). After a median follow-up of 5.3 years (3.3-7.2, max. 15.2 years), the primary efficacy end-points peak gradient (median 14mmHg, 9-28) and regurgitation (median 0.5, interquartile range 0-1, grade 0-3) showed good results but an increase over time. Freedom from death/explantation/endocarditis/bleeding/thromboembolism at 5years were 97.8±1.2/88.7±3.3/99.1±0.9/100 and 99.2±0.8%, respectively. Freedom from death/explantation/endocarditis/bleeding/thromboembolism at 10years were 96.3±1.9/67.1±8.0/93.6±3.9/ 98.6±1.4 and 86.9±11.6%, respectively. In total, 21 DAH were explanted. Seven were replaced by a mechanical AVR, 1 Ross operation was performed and a re-do DAH was implanted in 13 patients with no redo mortality. The calculated expected adverse events were lower for DAH compared to cryopreserved homograft patients (mean age 8.4 years), and in the same range as for Ross patients (9.2 years) and mechanical AVR (13.0 years). CONCLUSIONS: This large-scale prospective analysis demonstrates excellent mid-term survival using DAH with adverse event rates comparable to paediatric Ross procedures.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Allografts; Aortic valve disease; Children; decellularization